The Body Upon the (Lynching) Tree: the Humanity of Jesus in James Cone and Reinhold Niebuhr. (22nd December 2020) - Tafilowski, Ryan
Abstract: In The Cross and the Lynching Tree, James Cone addresses Reinhold Niebuhr's complicated record on the so-called 'Negro Question'. Although Niebuhr was keenly aware of and sensitive to black suffering and the systemic injustices which produced it, he failed to see any explicit relationship between the crucifixion of Jesus and the lynching of black persons. But what accounts for this failure? While Cone rightly posits Niebuhr's limited theological imagination and sparse contact with African Americans as contributing factors, this essay argues, first, that Niebuhr cannot connect cross and lynching tree because of an anaemic and implicitly docetic Christology. It then suggests, second, that only an anti-docetic Christology with a robust account of Jesus's humanity, such as Cone's, can interpret black suffering christologically. To state the thesis in Niebuhrian idiom: Niebuhr takes the humanity of Jesus literally, but not seriously, whereas Cone takes the blackness of Jesus's flesh seriously, but not literally.